Rickettsial infection in farmed Atlantic salmon in eastern Canada - Cusack, R. Roland (2002)
The cause of death in a postsmolt, Atlantic salmon population with elevated levels of mortalities was investigated. Diagnosis of a rickettsia-like organism was based on gross pathology, histopathology, differential staining, electron microscopy and fluorescent antibody tests. The course of the infection and response to treatment are discussed. This is the first reported occurrence of salmon rickettsias in the Atlantic coast of North or South America.